Evaluation of engine combustion and exhaust emissions characteristics using diesel/butanol blended fuel. (25th June 2019) - Yusri, I.M.; Mamat, Rizalman; Akasyah, M.K.; Jamlos, M.F.; Yusop, A.F.
Highlights: Butanol-diesel blends by 5%, 10% and 15% of butanol-to-diesel fuels. Increase of butanol in diesel fuels, resulted in a decreasing trend of combustion parameters. WPS was applied to investigate the engine cycle-to-cycle variations. Butanol addition reduced NOx, CO, and HC but produced increasing trend of CO2. Abstract: Depletion of non-renewable fuel sources accompanied with never-ending engine exhaust emissions pollution from internal combustion lead to renewed interests in alternative energy resources. Alcohol fuel had emerged as one of the viable candidates as a fuel substitute to reduce the use of fossil fuels in diesel engine. The aim of the experimental investigation is to study the effects of engine fuel properties characteristics towards engine combustion and exhaust emissions characteristics. In this experimental study, the diesel engine was tested at butanol/diesel percentage volume ratios of 5:95 (DBu5), 10:90 (DBu10) and 15:85 (DBu15) of butanol-to-diesel, respectively. Combustion analysis results showed that butanol/diesel blends have a lower in-cylinder pressure, rate of pressure rise and rate of heat release. Moreover, the mass fraction burned analysis shows longer ignition delay and burn duration. Apart from that, the wavelet power spectrum analysis suggested that DBu15 possesses high engine cyclic variations. The engine exhaust emissions show generally a reduction of nitrogen oxides, carbon monoxides and unburned hydrocarbon.